ANALISIS KESALAHAN TANDA BACA PADA KARANGAN SISWA KELAS VIII SMP NEGERI 3 SUMBAWA BESAR - Putra, Erwinsyah; Utami, Wiwik Surya (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research discusses the analysis of punctuation errors in the essays of class VII students at SMP Negeri 3 Sumbawa Besar. The aim of this research is to describe errors in the use of punctuation marks in the essays of class VIII students at SMP Negeri 3 Sumbawa Besar. The method used in this research is qualitative with a descriptive approach. The data collection technique used in this research is by explaining the types of essays to students, then collecting essays resulting from student assignments, then analyzing errors in the use of punctuation marks in these essays. The results of the research showed that there were 20 errors in the use of punctuation marks from the 25 students' essays collected, punctuation marks which dominated errors in periods were 10 errors, commas were 9 errors and quotation marks were 1 error.